2005
DOI: 10.1002/pi.1922
|View full text |Cite
|
Sign up to set email alerts
|

Effects of α‐form or β‐form nuclei on polymorphic crystalline morphology of poly(butylene adipate)

Abstract: The effects of α‐form and β‐form nuclei on polymorphic morphology of poly(butylene adipate) (PBA) upon recrystallization from the molten state up to various Tmax values were examined by differential scanning calorimetry (DSC), wide‐angle X‐ray diffraction (WAXD) and polarized light microscopy (PLM). In this study, PBA with complex melting and polymorphism behaviour was used as a model for examining different types and extents of residual nuclei. As the PBA initially containing the sole α‐crystal was brought to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
51
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 26 publications
2
51
0
Order By: Relevance
“…At T c = 30 o C where the (α + β) mixture develops, the neat PBA shown the ring band spherulite (a 1 ), Which is in good agreement with the previous reports 10,11,13. With increasing the T c to 35 o C, the spherulite size of the neat PBA increased and its spherulite density decreased (a 2 ).…”
supporting
confidence: 91%
See 1 more Smart Citation
“…At T c = 30 o C where the (α + β) mixture develops, the neat PBA shown the ring band spherulite (a 1 ), Which is in good agreement with the previous reports 10,11,13. With increasing the T c to 35 o C, the spherulite size of the neat PBA increased and its spherulite density decreased (a 2 ).…”
supporting
confidence: 91%
“…[3][4][5][6][7] Recently, much attention has been focused on the aliphatic polyester (including the PBA) due to the complicated, peculiar and interesting relationship among its polymorphic crystalline structure, multiple melting behavior, morphology, phase transition and property (biodegradability). [8][9][10][11][12][13][14] Depending on the melting-crystallization temperature (T c ), PBA can crystallize into the α modification (T c > 32 o C), β modification (T c < 29 o C), and the mixture of α and β modification ((α + β), 29 o C ≤ T c ≤ 32 o C). 8 The β modification exhibits a faster crystallization rate than the α one, and is considered as the kinetically preferential phase.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing the number of crystals using a specific polymorphic modification is a practical option for improving the performance of a polymeric material [129][130][131][132][133][134][135][136][137][138].…”
Section: Self-nucleation and Preferential Polymorphismmentioning
confidence: 99%
“…Other studies based on the SN and control of polymorphism were performed for polyamide 11 [131], poly(vinylidenefluoride) [135,136], poly(butylene adipate) [138], and chocolate [137].…”
Section: Self-nucleation and Preferential Polymorphismmentioning
confidence: 99%
“…10,11 On the other hand, during the melting recrystallization process, the remaining content of α-nuclei decides the final crystal form of PBA regardless of crystallization temperature. 12 The recent research in our lab found that the molecular weight and its distribution also had a significant influence on the polymorphic crystals of PBA. 8 …”
Section: Introductionmentioning
confidence: 99%